Distribution of human rotaviruses, especially G9 strains, in Japan from 1996 to 2000 - Zhou Y. (2014)
A 4-year (1996-2000) survey of rotavirus infection involving 2,218 diarrheal fecal specimens of children collected from five regions of Japan was conducted. A total of 642 (28.9%) specimens were found to be rotavirus positive. A changed prevalence pattern of rotavirus G serotype was found with an increase of G9 and G2 and a decrease of G1, although G1 remained the prevailing serotype. Serotype G9 was unexpectedly determined to be the prevailing serotype in Sapporo (62.5%) and Tokyo (52.9%) in 1998-1999, and in Saga (78.4%) in 1999-2000. G9 strains isolated from 1998-1999 belonged to the P[8] -NSP4-Wa-group with long RNA pattern, while, G9 strains isolated from 1999-2000 belonged to three groups, the P[8]-NSP4-Wa-group with long RNA pattern, the P[4]-NSP4-KUN-group with short RNA pattern and a mixed-type group (P[4]/P[8]-NSP4-KUN/Wa-group with long RNA pattern). Both sequence and immunological analysis of VP7 revealed that the G9 strains from 1999-2000 were much more closely related to the G9 strains isolated worldwide in the 1990s, including G9 strains found in Thailand in 1997. However, the G9 strains from 1998-1999 were distinct from these and more closely related to the G9 prototype strains F45, AU32 and WI61 discovered in Japan and the US in the 1980s. Thus the G9 strains isolated in 1998-1999 had progenitors common to the G9 prototype strains, while the strains isolated in 1999-2000 did not directly evolve from them but were related to global G9 strains that have emerged in recent years. These data supported our previous report that G9 rotavirus might exist as two or more subtypes with diverse RNA patterns, P-genotype and NSP4 genogroup combinations (Y.M. Zhou et al., J. Med. Virol. 65: 619-628, 2001) and suggested that G9 rotavirus prevalent in Japan during two successive years belonged to different subtypes. The nucleotide sequences presented in this paper were submitted to DDBJ, EMBL and GenBank nucleotide sequence databases. The accession numbers are: 00-Ad2863VP7 (AB091746), 00-OS2986VP7 (AB091747), 00-SG2509VP7 (AB091748), 00-SG2518VP7 (AB091749), 00-SG2541 (AB091750), 00-SG2864 (AB091751), 00-SP2737VP7 (AB091752), 99-SP1542VP7 (AB091753), 99-SP1904VP7 (AB091754), 99-TK2082VP7 (AB091755) and 99-TK2091VP7 (AB091756).